“PENGARUH MOTIVASI, DAN KOMPETENSI PARAMEDIS TERHADAP TINGKAT KEPUASAN PASIEN RAWAT INAP DI RUMAH SAKIT BHAYANGKARA KOTA PADANG” - Arivetullatif Arivetullatif (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Based on the results of the research on the influence of motivation on the level of satisfaction of inpatients at the bhayangkara hospital in Padang city with paramedic competencies as a moderating variable, it can be concluded that paramedic motivation has a positive and significant effect on inpatient satisfaction at the Bhayangkara Hospital in Padang City with Sig = 0,000). Competence directly without effect on patient satisfaction can be proven by the influence value of 0.010 (Sig = 0.106). Motivation has a significant Sig = 0,000 value, so it is stated that, competency variables can function as moderating variables.